PENERAPAN METODE PETA PIKIRAN (MIND MAPPING) UNTUK PENINGKATAN KETERAMPILAN MENULIS NARASI SISWA KELAS IV SEKOLAH DASAR - MIFTACHURROCHMAH, DAHLIA (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: Application of Mind Mapping Method in Improving Writing Skill Narrative 4th Grade Student of Elementary School Kalirancang 3 in Year 2012/2013. This study aimed to (1) to describe the steps in the method of Mind Mapping narrative writing skills outcomes of primary school fourth grade students,(2) describe the problems and their solutions in the applications of Mind Mapping method in improving narrative writing skills in 4th grade student. This research subjects is the fourth grade of three elementary school Kalirancang, total of twenty eight students. The experiment was conducted in three cycles, with each cycle consisting of planning, action, observation, and reflection. Data collection technique is to test, observation, and documentation. The validity of the data using triangulation method. Data analytis with qualitative and quantitative. The result show that Mind Mapping application method in accordance with the steps can increase students narrative writing skills of fourth grade, so as to improve writing skills. The percentage gain in the first cycle was 92,85%, an increase on the second and third cycle to 96,42%. Keywords: Mind Mapping, Improving skills, Narrative Writing Abstrak: Penerapan Metode Peta Pikiran (Mind Mapping) untuk Peningkatan Keterampilan Menulis Narasi di Sekolah Dasar. Penelitian ini bertujuan untuk (1) mendeskripsikan penerapan Metode Peta Pikiran (Mind Mapping) dalam peningkatan keterampilan menulis narasi siswa kelas IV sekolah dasar. (2) mendeskripsikan kendala dan solusi penerapan metode Peta Pikiran (Mind Mapping) dalam peningkatan keterampilan menulis narasi di kelas IV sekolah dasar. Subjek penelitian ini adalah siswa kelas IV SDN 3 Kalirancang sejumlah 28 siswa. Penelitian dilaksanakan dalam tiga siklus, dengan tiap siklus terdiri atas perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Teknik pengumpulan data adalah dengan tes, observasi, dan dokumentasi. Validitas data menggunakan metode triangulasi. Analisis data yang digunakan dengan analisis kualitatif dan kuantitatif. Hasilnya menunjukkan bahwa penerapan metode Peta Pikiran (Mind Mapping) yang sesuai dengan langkah-langkah dapat meningkatkan keterampilan menulis narasi siswa kelas IV SD, sehingga dapat meningkatkan keterampilan menulis. Presentase perolehan pada siklus I adalah 92,85%, meningkat pada siklus II dan siklus III menjadi 96,42%. Kata kunci: Metode Mind Mapping, Peningkatan Keterampilan, Menulis Narasi.